Privatization effects on Zakat and dividend: Empirical evidence from Malaysia and Jordan - Bakar, Ridzwan; Neman Darwazeh, Riyad Neman Darwazeh; Sakinah, Wardah Sakinah2 (Journal of Entrepreneurship, Business and Economics, 2016)
There is a growing consensus in the literature that privatization program has positive impact to the country’s productivity and competitiveness. At micro level, empirical analyses both in Malaysian and Jordan have shown the significant contribution of privatization program on firms’ profitability, productivity and better leverage. Generally, privatization leads to better profitability which theoreti-cally should provide higher return to shareholders in terms of dividend as well as higher contribution to stakeholders in terms of zakat to the asnaf (zakat recipients including the poor and needy). Howev-er, studies on privatization impact towards zakat and dividend payment are almost absent. Therefore, this study aims at investigating the effect of privatization on zakat and dividend disbursement. This paper focuses on two developing nations namely Malaysia and Jordan. The sample size of this analy-sis includes 17 Malaysia Government Link Corporations (Top GLC20 companies) and 23 Jordan State Owned Enterprises (SOEs). The duration of the study is eleven (11) years from 2003 to 2013. The data were collected from Bloomberg, Amman Stock Exchange and Bursa Malaysia. Using statis-tical models and Wilcoxon signed rank test, the results show that privatization has contributed to higher payment in terms of dividend to shareholders in both countries. In addition, zakat paid by Ma-laysian GLCs is steadily increasing and significant. The findings also indicate that global financial crisis 2007-2008 has no impact on corporate zakat payable in Malaysia, while dividend growth is slow during this period. The paper then provides discussion on few pertinent issues and finally sug-gests the need for new tax and zakat Law in Jordan as well as improvement in current zakat account-ing practices in Malaysia. Research paper Reference to this paper should be made as follows: Bakar, R, Darwazeh, R. N., Sakinah, W. (2016). “Privatization effects on Zakat and dividend: Empirical evidence from Malaysia and Jordan”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 1, pp. 1–21